Pastoralism and milk production - Nicholson, M.J. (Edinburgh University, 1985)
Describes generally the parameters of pastoralist milk production w. partic. ref. to cattle. Discusses briefly methods of determining milk yield and milk offtake and the effect of milk production on reproductive rate. Gives a brief description of lactation curve, lactation length, calf growth and camel & small stock milk.